Enhancing 21st Century Skills in Students with Special Needs Through STEM Learning - Sarita, Maya Rahma; Wisudawati, Asih Widi (JTK (Jurnal Tadris Kimiya), 2024)
STEM learning has been recognized for its potential to improve critical, creative, collaborative, and communicative skills—key components of 21st-century competencies. For students with special needs, STEM-based approaches can offer tailored opportunities to develop these skills through active and interactive learning methods. This study aims to identify patterns of STEM learning implementation that contribute to the development of 21st-century skills in students with special needs. A descriptive qualitative approach was employed, involving data collection from Giwangan State Elementary School in Yogyakarta. Respondents included a teacher and a special assistant teacher for the 4th grade. Data collection techniques consisted of field observations, semi-structured interviews with 18-27 questions, and document analysis. The data were analyzed using qualitative content analysis, including reduction, presentation, and conclusion drawing, while validity was ensured through source triangulation. The findings reveal that STEM learning is conducted in three stages: introductory, main, and closing phases. This method engages students with special needs in problem-solving and group projects integrating science, technology, engineering, and mathematics. The observed activities enhanced students' motivation, interest in learning, and the development of critical thinking, collaboration, and communication skills. The study highlights the effectiveness of STEM learning in fostering 21st-century skills among students with special needs, offering an inclusive and interactive framework for educators to implement in similar contexts.